Identification and characterization of Rubisco activase genes in Oryza punctata. Issue 3 (7th March 2017) - Xu, Si; Qin, Zong‐Yan; Gong, Pi‐Chang; Dong, Qian‐Li; Bao, Ying
Abstract: Rubisco activase (Rca), a specific chaperone, catalyzes the in vivo activation of Rubisco, and thus plays a major role in plant photosynthesis. Although the genes encoding Rubisco activase have been studied in many model or economic plants, few studies have analyzed their homologs in plants of closely related crop species. In this study, an Rca gene was identified and characterized in a wild relative of rice, Oryza punctata Kotschy ex Steud. The gene was 2747 bp long and possessed six exons and five introns with 47% GC content. Furthermore, cDNA sequencing produced two transcripts, RcaL and RcaS, that differed in the sequence by an inclusion of 99 bp at the carboxy terminus of RcaL . Sequence comparison between the two transcripts and the genomic DNA showed that there was a 20‐bp alternative splicing event that occurred at the fifth intron of the gene leading to the synthesis of a short polypeptide. The leaf transcriptome analysis showed that RcaS had a higher expression level than that of RcaL in a normal growth environment. In addition, the yeast two‐hybrid assays showed the small isoform of Rubisco activase in close contact with the large subunit of the Rubisco in this species, supporting the side‐on binding model of interaction between two proteins. This study broadens our understanding of the molecular characteristics of some essential genes in photosynthesis.